Wall Street's think tank : the Council on Foreign Relations and the Empire of Neoliberal Geopolitics, 1976-2014 - Shoup, Laurence H. (Monthly Review Press, 2015)
The Council on Foreign Relations is the most influential foreign-policy think tank in the United States, claiming among its members a high percentage of government officials, media figures, and establishment elite. For decades it kept a low profile even while it shaped policy, advised presidents, and helped shore up U.S. hegemony following the Second World War. In 1977, Laurence H. Shoup and William Minter published the first in-depth study of the CFR, Imperial Brain Trust, an explosive work that traced the activities and influence of the CFR from its origins in the 1920s through the Cold War.